Моніторинг поведінки водія при управлінні транспортним засобом за допомогою eye tracking системи - Гречмак, Д. В. (ХНУРЕ, 2020)
Today, there are not many methods of monitoring driver behavior when driving a vehicle. Almost everyone who owns a car has a smartphone. The smartphone is equipped with a front camera and a display that allows you to scan your face and display information. There are also speakers in each smartphone that allow you to alert the driver to beeps. The paper proposes a new method of monitoring the condition of the driver through a smartphone.
Keywords: eye-tracking